Functional Characterization of Cucumis metuliferus Proteinase Inhibitor Gene (CmSPI) in Potyviruses Resistance - Lin, Chia-Wei (Viruses, 2015)
Proteinase inhibitors are ubiquitous proteins that block the active center or interact allosterically with proteinases and are involved in plant physiological processes and defense responses to biotic and abiotic stresses. The CmSPI gene identified from Cucumis metuliferus encodes a serine type PI (8 kDa) that belongs to potato I type family. To evaluate the effect of silencing CmSPI gene on Papaya ringspot virus resistance, RNA interference (RNAi) with an inter-space hairpin RNA (ihpRNA) construct was introduced into a PRSV-resistant C. metuliferus line. CmSPI was down-regulated in CmSPI RNAi transgenic lines in which synchronously PRSV symptoms were evident at 21 day post inoculation. Alternatively, heterogeneous expression of CmSPI in Nicotiana benthamiana was also conducted and showed that CmSPI can provide resistance to Potato virus Y, another member of Potyvirus, in transgenic N. benthamiana lines. This study demonstrated that CmSPI plays an important role in resistant function against potyviruses in C. metuliferus and N. benthamiana.